Comparison of Bamboo and Wire Types of Battery Materials on the Welfare and Production Performance of Laying Hen - Yulianti, Dyah Lestari; Nurwahyuni, Eka; Akbar, Muhammad Faisal (CV. Komunitas Dunia Peternakan, 2024)
This research aimed to determine the comparison of types of battery materials for laying hens, specifically bamboo and wire, on the welfare and production performance of laying hens. The material for this research consisted of 100 laying hens of the ISA Brown strain aged 54 weeks. The variables observed included livestock welfare, which was assessed through behavioral aspects (eating, drinking, and resting), while the production performance variables observed included HDP (Hen Day Production), egg weight, egg mass, and FCR (Feed Conversion Ratio). The research method employed an experimental approach using the T-test (independent sample). Two treatments were used, each with 50 replications. The results of the research indicated that the difference in treatment using T1 (bamboo battery materials) and T2 (wire battery materials) affected livestock welfare and production performance. The research results demonstrated that the behavior of bamboo batteries was considered better in terms of livestock welfare because they were able to better prevent heat stress. In terms of production performance, wire batteries exhibited higher Hen Day Production (HDP) and were better at preventing disease than bamboo batteries. However, bamboo batteries had a higher egg weight due to the frequency of feeding chickens being higher than wire batteries. Improved sanitation management is necessary for batteries made from bamboo because they tend to more easily become a medium for the growth of germs, lice, and fungi, which can cause disease and result in decreased production performance.